Three new species of the free-living marine nematode Metoncholaimus Filipjev, 1918 (Enoplida, Oncholaimidae) from Argentinean coasts - Russo, Virginia Lo; de Ward, Catalina T. Pastor (Zootaxa, 2019)
Three new species of free-living marine nematodes of the genus Metoncholaimus are described from San Matías gulf (Río Negro, Argentina). Metoncholaimus sanmatiensis sp. n. is characterized by large body size, long spicules, small gubernaculum, presence of long setose pre- and postcloacal genital sensilla and presence of precloacal pores. Metoncholaimus perdisus sp. n. is characterized by small-sized body, short spicules, small gubernaculum, presence of long setose pre- and postcloacal genital sensilla and presence of pre- and postcloacal pores. Metoncholaimus paracavatus sp. n. is closely related to Oncholaimus cavatus but can be considered as a new Metoncholaimus species based on the presence of gubernaculum and the morphology of the demanian system. A compendium of all valid species, including new species, is given.